Can community health centers improve the self-rated health of migrants? Evidence from China - Ai-Lin Mao; Yu-Kun Tian; Ya-Nan Li (Frontiers Media S.A., 2022)
BackgroundDue to the "epidemiological paradox," migrants face the risk of health attrition during their migration. Meanwhile, institutional constraints cause a health gap between migrants and non-migrants. To narrow this gap and maintain equity, scholars have studied the role and impact mechanism of medical insurance participation in improving the health of migrants. However, due to the provision of China's basic medical insurance system, the proportion of migrants participating in employee medical insurance is still relatively low, while the community health center (CHC) is a more accessible medical resource for this group. Therefore, this study attempts to explore the impact of CHCs on the self-rated health (SRH) of migrants and identify the factors and mechanisms associated with such an impact. This study addresses the hypotheses whether (a) CHCs can significantly improve the SRH of migrants in China and (b) CHCs improve the SRH of migrants by promoting both their health knowledge and health behavior.MethodsData was obtained from the 2017 China Migrants Dynamic Survey (CMDS). From the survey, 127,687 migrants were identified, and a series of logit regressions were conducted to explore the correlation between CHCs and the SRH of migrants. Propensity score matching (PSM) logit was also used for the robustness tests.ResultsLogit estimations revealed that CHC is positively related to the SRH of migrants (OR = 1.095, p < 0.001). Compared to others, males (OR = 1.156, p < 0.001), younger people with higher education (OR = 1.027, p < 0.001), more stable employment (OR = 1.544, p < 0.001), and people with a lower proportion of elderly (> 65 years) household family members (OR = 0.842, p < 0.001) tended to have better SRH. The results also showed that the impact of CHCs on migrants' SRH varied by gender, age, and income (p < 0.001). A possible mechanism is that CHCs can improve migrants' SRH by promoting both their health knowledge and health behaviors.ConclusionPrograms that strengthen health knowledge and policies to enhance access to healthcare could be prioritized to improve the SRH of migrants in China.